2021
DOI: 10.4251/wjgo.v13.i7.716
|View full text |Cite
|
Sign up to set email alerts
|

High expression of protein phosphatase 2 regulatory subunit B'' alpha predicts poor outcome in hepatocellular carcinoma patients after liver transplantation

Abstract: BACKGROUND Protein phosphatase 2 regulatory subunit B'' alpha ( PPP2R3A ) gene has been reported in other tumors, but the influence of PPP2R3A gene expression on the occurrence, development, and prognosis of hepatocellular carcinoma (HCC) remains unclear. AIM To investigate whether the PPP2R3A gene could be used to predict tumor recurrence and survival of HCC patients after liver transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Further studies have found that PPP2R3A gene overexpression promotes HK1 levels and glycolysis, thereby promoting the proliferation, invasion and migration of hepatocellular carcinoma (45). Additionally, PPP2R3 expression is associated with poor prognosis after liver transplantation in hepatocellular carcinoma patients (46). However, the role of PPP2R3A in pancreatic cancer is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have found that PPP2R3A gene overexpression promotes HK1 levels and glycolysis, thereby promoting the proliferation, invasion and migration of hepatocellular carcinoma (45). Additionally, PPP2R3 expression is associated with poor prognosis after liver transplantation in hepatocellular carcinoma patients (46). However, the role of PPP2R3A in pancreatic cancer is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The promoting effects of PR72 on proliferation can also be observed in recent tumor biology studies. For instance, high expression of the PPP2R3A gene was found to be directly linked to the outcome of patients with hepatocellular carcinoma ( 37 ), which correlates with promotion of glycolysis via regulation of hexokinase 1 ( 38 ). Conversely, silencing of the PPP2R3A gene abolished glycolysis as well as proliferation, migration, and invasion in liver tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent advances in our approach to studying these subunits have revealed that posttranslational processes can impact not only the activity, but also the intracellular targeting and substrate specificity of the PP2A heterotrimer. Thus far, this has been demonstrated mainly for subunits belonging to the B and B' families (34)(35)(36). While early basic biochemical experiments have shown that PR72, a member of the B'' gene family, plays a role in regulating PP2A activity in response to varying Ca 2+ concentrations (8,9), comprehensive functional findings in both healthy and diseased hearts are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…These include the B-type subunits PPP2R2D in gastric cancer and PR130 (encoded by the gene PPP2R3A) in liver cancer. [22][23][24][25][26] A recent work analyzed Cancer-Genome-Atlas (TCGA) datasets and surgically removed human PDACs for a link between the PPP2R3A mRNA expression and PR130 with patient survival. PR130 was found to be associated with poor prognosis and with tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%